Let [tex] \rm|M|[/tex] denote the determinant of a square matrix M. Let [tex] \rm g : \bigg[0, \dfrac{\pi}{2} \bigg] \to \mathbb{R}[/tex] be the function defined by [tex] \rm g( \theta) = \sqrt{f( \theta) - 1} + \sqrt{f \bigg( \dfrac{\pi}{2} - \theta\bigg) - 1} [/tex] where
[tex] \rm f( \theta) = \dfrac{1}{2} \left| \begin{matrix} 1& \sin( \theta) &1 \\ - \sin( \theta) &1& \sin( \theta) \\ - 1& - \sin( \theta)&1 \end{matrix} \right | + \left| \begin{matrix} \sin(\pi) & \cos( \theta + \frac{\pi}{4} ) & \tan( \theta - \frac{\pi}{4} ) \\ \sin( \theta - \frac{\pi}{4} ) & - \cos( \frac{\pi}2 ) & \log_{e} ( \frac{4}\pi ) \\ \cot( \theta + \frac{\pi}{4} ) & \log_{e} ( \frac{\pi}4 )& \tan(\pi) \end{matrix} \right | [/tex]
Let p(x) be a quadratic polynomial whose roots are the maximum and minimum values of the function g([tex]\theta [/tex]) , and p(2)=2-[tex]\sqrt{2}[/tex]. Then which of the following is True?

[tex] \rm(1) \: p \bigg( \frac{3 + \sqrt{2} }{4} \bigg) < 0 \\ \rm(2) \: p \bigg( \frac{1 + 3 \sqrt{2} }{4} \bigg) > 0 \\ \rm(3) \: p \bigg( \frac{5\sqrt{2} - 1 }{4} \bigg) > 0 \\ \rm(4) \: p \bigg( \frac{5 - \sqrt{2} }{4} \bigg) < 0[/tex]

ā€‹

Let tex rmMtex denote the determinant of a square matrix M Let tex rm g bigg0 dfracpi2 bigg to mathbbRtex be the function defined by tex rm g theta sqrtf theta class=

Respuesta :

The second matrix in the definition of [tex]f[/tex] is singular, since

[tex]\sin(\pi) = -\cos\left(\dfrac\pi2\right) = \tan(\pi) = 0[/tex]

[tex]\cos\left(\theta+\dfrac\pi4\right) = \sin\left(\dfrac\pi2 - \left(\theta+\dfrac\pi4\right)\right) = \sin\left(\dfrac\pi4-\theta\right)=-\sin\left(\theta-\dfrac\pi4\right)[/tex]

[tex]\cot\left(\theta+\dfrac\pi4\right) = \tan\left(\dfrac\pi2 - \left(\theta+\dfrac\pi4\right)\right) = \tan\left(\dfrac\pi4 - \theta\right) = -\tan\left(\theta-\dfrac\pi4\right)[/tex]

[tex]\ln\left(\dfrac4\pi\right) = -\ln\left(\dfrac\pi4\right)[/tex]

In other words, it's antisymmetric; [tex]A^\top=-A[/tex]. It's easy to show that [tex]\det(A)=0[/tex] if [tex]A[/tex] is 3x3 and antisymmetric.

The other determinant reduces to

[tex]\begin{vmatrix}1 & \sin(\theta) & 1 \\ - \sin(\theta) & 1 & \sin(\theta) \\ -1 & -\sin(\theta) & 1 \end{vmatrix} = 2 + 2\sin^2(\theta)[/tex]

Hence

[tex]f(\theta) = 1 + \sin^2(\theta) \implies f\left(\dfrac\pi2\right) = 1 + \cos^2(\theta)[/tex]

With [tex]g[/tex] defined on [tex]\left[0,\frac\pi2\right][/tex], both [tex]\sin(\theta)[/tex] and [tex]\cos(\theta)[/tex] are non-negative. So

[tex]g(\theta) = \sqrt{f(\theta)-1} + \sqrt{f\left(\dfrac\pi2-\theta\right)-1} \\\\ ~~~~ = \sqrt{\sin^2(\theta)} + \sqrt{\cos^2(\theta)} \\\\ ~~~~ = |\sin(\theta)| + |\cos(\theta)| \\\\ ~~~~ = \sin(\theta) + \cos(\theta) \\\\ ~~~~ = \sqrt2\,\sin\left(\theta + \dfrac\pi4\right)[/tex]

which is maximized at [tex]t=\frac\pi4[/tex] with a value of [tex]\sqrt2\,\sin\left(\frac\pi2\right)=\sqrt2[/tex], and minimized at [tex]t=0[/tex] and [tex]t=\frac\pi2[/tex] with a value of [tex]\sqrt2\,\sin\left(\frac{3\pi}4\right)=1[/tex].

Edit: The rest of my answer wouldn't fit. Continued in attachment.

Ver imagen LammettHash
ACCESS MORE